Milho consorciado com guandu-anão em diferentes arranjos de plantas em sistema orgânico - Gallo, Anderson de Souza (2016)
The corn is among the crops produced more in intercropping systems, mainly due to its architecture and ecophysiology. The objective of the study was to evaluate the growth, productivity and nutritional status of maize in intercropping with dwarf pigeon pea in different arrangements of plants. The study was conducted in the experimental area of Center of Agricultural Sciences, Federal University of São Carlos, Araras, SP, in a soil classified as Oxisoil, clayey. The experimental lineation was a randomized block design with six treatments and four replications. The treatments consisted of different arrangements of dwarf pigeon pea in consortium with corn: corn alone; dwarf pigeon pea sown in row planting corn; a line of planted dwarf pigeon pea in corn leading; two rows of dwarf pigeon pea sown between rows of corn; dwarf pigeon pea sown in lines and lines of corn and dwarf pigeon pea sown in line and two lines between the rows of corn. The growth of corn plants was not affected by consortia adopted. The arrangement with dwarf pigeon pea sown in line and two lines between the rows of corn increased leaf nitrogen content in maize plants compared to other arrangements and corn alone. As for the foliar potassium and calcium were higher in corn alone and treatment with dwarf pigeon pea sown in row planting corn. Corn consortia with the dwarf pigeon pea sown in line and two lines between the rows had grain yield higher than other arrangements and maize grown in monoculture.